Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Tematik Terpadu Menggunakan Model Make a Match di Sekolah Dasar - Ghenny Rizalma; Hamimah Hamimah (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research on integrated theatrical learning in class IV is a dilator behind the still low learning outcomes of students in integrated thematic learning. The purpose of this study was to describe planning, implementation, and integrated thematic learning outcomes using models Make a Match in class IV SD Negeri 17 Batu Gadang Sungaipua District. This type of research is Classroom Action Research (CAR) using a qualitative and quantitative approach. The research subjects were class IV students with 24 people, 14 men and 10 women. The study was conducted in two cycles. The results of the first cycle of research obtained an average of 84.08% (Good) and increased in the second cycle to 93.18% (Very Good). Implementation in the aspect of teacher activity cycle I obtained an average of 80.35% (Good) and increased in the second cycle to 96.42% (Very Good). The implementation of the activity aspects of students in the first cycle obtained an average of 80.35% (Good) and increased in the second cycle to 96.42% (Very Good). The learning outcomes of students in the first cycle obtained an average of 76.62 (enough) and increased in the second cycle to 91.69 (good). Thus the Make a Match type cooperative model can improve the integrated thematic learning outcomes of fourth grade students of SDN 17 Batu Gadang Sungaipua District.